Light‐Triggered Drug Release from Red Blood Cells Suppresses Arthritic Inflammation. Issue 1 (13th October 2021) - Zywot, Emilia M.; Orlova, Natalia; Ding, Song; Rampersad, Rishi R.; Rabjohns, Emily M.; Wickenheisser, Victoria A.; Wang, Qunzhao; Welfare, Joshua G.; Haar, Lauren; Eudy, Amanda M.; Tarrant, Teresa K.; Lawrence, David S.
Abstract: Arthritis is a leading cause of disability in adults, which can be intensely incapacitating. The location and intensity of the pain is both subjective and challenging to manage. Consequently, patient‐directed delivery of anti‐inflammatories is an essential component of future therapeutic strategies for the management of this disorder. The design and application of a light‐responsive red blood cell (RBC)‐conveyed dexamethasone (Dex) construct that enables targeted drug delivery upon illumination of the inflamed site is described. The red wavelength (650 nm) responsive nature of the phototherapeutic is validated using tissue phantoms mimicking the light absorbing properties of various skin types. Furthermore, photoreleased Dex has the same impact on cellular responses as conventional Dex. Murine RBCs containing the photoactivatable therapeutic display comparable circulation properties as fluorescently labeled RBCs. In addition, a single dose of light‐targeted Dex delivery is fivefold more effective in suppressing inflammation than the parent drug, delivered serially over multiple days. These results are consistent with the notion that the circulatory system be used as an on‐command drug depot, providing the means to therapeutically target diseased sites both efficiently and effectively. Abstract : Red blood cells containing a dexamethasone (Dex)‐vitamin B12‐Cy5 conjugate serve as a circulating drug depot that releases Dex, an anti‐inflammatory agent, upon exposure to red light (650 nm). The photoactivatable therapeutic construct displays anti‐inflammatory efficacy in a rheumatoid arthritis mouse model